Composition and maternal origin of the neonatal oral cavity microbiota. Issue 1 (1st January 2019) - Tuominen, Heidi; Collado, Maria Carmen; Rautava, Jaana; Syrjänen, Stina; Rautava, Samuli
ABSTRACT: Background: The origin of the initial oral microbiota in neonates still remains poorly understood. Objective : The aim of this study was to understand how the maternal microbiota contributes to the initial neonatal oral microbiota. Design : Twelve mother-neonate pairs with samples from the maternal oral mucosa, uterine cervix and placenta and the neonatal oral cavity immediately after birth were studied. The microbiota composition and diversity were characterized by 16S rRNA gene sequencing (V3-V4 region). The microbiota analyses and comparisons were carried out with Calypso software version 8.1 and with SourceTracker 1.0.1. Results : Samples from the neonatal oral cavity showed moderately high bacterial diversity and low richness. The neonatal oral cavity microbiota seems to share features mainly with the microbes detected in the placenta, followed by the cervical microbiota and the maternal oral microbiota. No statistically significant differences in diversity (Shannon index, p = 0.14), richness (Chao1, p = 0.53) or in microbial composition were observed according to delivery mode. Conclusion: The neonatal oral cavity microbiota is not significantly modulated by the birth canal or maternal oral microbiota but displays clear associations with microbes in the placenta. These results suggest that the neonatal oral microbiota may have a prenatal origin.